THE EFFECT OF HONEY BASTING TOWARD THE SAVINGS OF SMOKED CATFISH (Pangasius hypophthalmus) - Faisal Muhammad; Edison '; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Based from result of the research that 15 % honey basting toward smoked catfishcould increase the quality based from organoleptic value, chemical malue, pH value, sugarcontent, fungi identification and total of bacteria colonies. The results showed that theprocess of honey basting had a significant effect toward the appearance value, texture, taste,moisture content, protein content, fat, ash content, sugar content, and total of bacteriacolonies, without any effect toward smell content and pH value. Honey basting 15% increasethe organoleptic value quality of 7.02 on appearance value, 8.06 on textute, 7.68 on smell,and 7.64 on taste, with the bright brown color of the smoked fish, dense and compact texture,distinctive odor of smoked fish and have a good characteristic flavor of smoked fish. Thesmoked catfish contained 23.35% of moisture content, 37.10% of protein content, 14.49% offat, 5.37% of ash content, 7.22 of pH, 18.35 of sugar content, and 2.0 x 104 cell/gram of thetotal of bacteris colonies, could maintain the saving of smoked catfish (Pangasiushypophthalmus).Keywords: Catfish, coconut shell, honey